IMPROVING MECHANISMS OF EFFECTIVE USE OF BUDGET FUNDS FROM STATE-OWNED ENTERPRISES (World Bulletin of Management and Law, 2023)
The article improving mechanisms of effective use of budget funds from stateowned enterprises is widely covered.State-owned enterprises(SOEs) are classified asthose enterprisesinwhich the state exerts significant control through full, majority, or significant minority ownership. This definition includes SOEs that are owned by the central or federal government as well asthe ones owned by regional and local governments(Sturesson, McIntyre, and Jones 2015). Despite a wave of privatization in the last 3 decades, SOEs still contribute significantly to economic growth of both developed and developing countries (Robinett 2006).